Stability of piecewise polynomial collocation for Volterra integro‐differential equations - Oja, P.; Tarang, M. (Mathematical Modelling and Analysis, 2001)
Numerical stability of the spline collocation method by piecewise polynomials for Volterra integro‐differential equations is investigated. Stability conditions depending on collocation parameters and also on parameters of certain test equation are obtained. Results of several numerical tests are presented supporting theoretical results. Kolokacijų metodo stabilumas Voltero tipo integro0diferencialinėms lygtims Sanrauka. Voltero tipo integro‐diferencialinė lygtis sprendžiama kolokacijų metodu. Ištirtas metodo stabilumas, kai naudojami trūkūs splainai. Parodyta, kad stabilumas priklauso nuo kolokacinių parametrų ir nuo vienos tęstinės lygties parametrų. Pateikiami skaičiavimo eksperimento rezultatai, kurie patvirtina visus teorinius teiginius. First Published online: 14 Oct 2010